Visualizing the past : the power of the image in German historicism - Maurer, Kathrin (Interdisciplinary German cultural studies, 2013)
Visual media had a decisive impact on how the past was perceived in 19th-century Germany. The panorama, photography, and book illustrations can portray the past spatially. By investigating the visual vocabulary of different historicist genres (illustrated history books, maps, historiography), this volume expands an understanding of German historicist culture as a multi-medial phenomenon. It demonstrates that the image works as a powerful tool to propagate the ideology of German imperialism, but also can critically reflect the political agendas of national historicism.